Perbandingan Aktivitas Antioksidan Ekstrak Etil asetat dan Metanol Daun Tumbuhan Matoa (Pometia pinnata) - Situmeang, Boima; Musa, Weny JA; Mulyadi, Agus; Ibrahim, Agus Malik; Widiyanto, Holisha; Bialangi, Nurhayati (Jurnal Penelitian Sains, 2024)
Matoa (Pometia pinnata) is a plant from the Sapindaceae family that is widely distributed throughout the Asia-Pacific region, including Indonesia, Malaysia, Thailand, and Sri Lanka. In Indonesia, the Matoa plant is commonly found in Java, Sumatra, and Papua. Empirically, the leaves of the Matoa plant have been utilized by the community as a traditional remedy for treating hypertension, fever, and diarrhea. The aim of this study was to test the antioxidant activity of ethyl acetate extract and methanol extract of Matoa leaves. Extraction was performed using the maceration method. The antioxidant activity was evaluated using UV-Visible spectroscopy. The free radical used was DPPH at a concentration of 50 ppm. The absorbance was measured at a wavelength of 517 nm. The antioxidant activity of the ethyl acetate extract of Matoa leaves was 38.87 ppm and 37.73 ppm. The antioxidant activity of the methanol extract of Matoa leaves was 27.99 ppm and 33.25 ppm. Based on the antioxidant activity values, both the ethyl acetate and methanol extracts of Matoa leaves have the potential as a source of natural antioxidants.